Building digital government strategies : principles and practices /: principles and practices. ([2017]) - Sandoval-Almazán, Rodrigo; Luna-Reyes, Luis F; Luna Reyes, Dolores E; Gil García, José Ramón; Purón Cid, Gabriel; Picazo-Vela, Sergio
No abstract available